2015
DOI: 10.1021/cs501705b
|View full text |Cite
|
Sign up to set email alerts
|

Hydroamination of C–C Multiple Bonds with Hydrazine Catalyzed by N-Heterocyclic Carbene–Gold(I) Complexes: Substrate and Ligand Effects

Abstract: In this work, we computationally address, from DFT calculations, mechanistic issues of the recently described hydroamination reactions catalyzed by (carbene) gold(I) complexes that use hydrazine as N-nucleophile. We have explored the hydrohydrazination of alkynes, alkenes, and allenes using three gold− carbene catalysts reported by Bertrand's and Hashmi's groups. Aspects such as the associative or dissociative nature of the ligand exchange between hydrazine and the substrate, the generation of the catalyticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 126 publications
1
46
0
Order By: Relevance
“…Thus, for example, high energies of activation (78–82 kcal mol –1 ) have been calculated for chloride dissociation in a series of [(NHC)AuCl] complexes. 89 …”
Section: Ligand Substitution and Activation Of Gold( I mentioning
confidence: 99%
“…Thus, for example, high energies of activation (78–82 kcal mol –1 ) have been calculated for chloride dissociation in a series of [(NHC)AuCl] complexes. 89 …”
Section: Ligand Substitution and Activation Of Gold( I mentioning
confidence: 99%
“…However, a subsequent computational study performed on the same reaction, while confirming on the one hand that the formation of such dinuclear gold alkynyl complexes was favored, also concluded that they were not the catalytically competent species [73]. Instead, the catalytic cycle matched the one presented in Scheme 2, and other thorough mechanistic studies performed using ammonia or hydrazine as a nucleophile (Scheme 13) [74,75] confirmed this substantial similarity, at least for what it concerns the initial steps of the catalytic cycle. Thus, in spite of the strong coordinating power possessed in particular by ammonia, the reaction goes through an external nucleophilic attack of the nitrogen nucleophile to a mononuclear, cationic-complex of the alkyne with gold.…”
Section: Hydroaminationmentioning
confidence: 81%
“…In particular, the presence of a basic nitrogen nucleophile in great excess with respect to the counteranion will make the former more likely to play a role in the proton transfer and protonolysis steps of the reaction. Indeed, computational studies favor this hypothesis [75]. Consequently, the only effect that the counteranion will exert will be in the competition for coordination to gold, and indeed in the few cases in which this effect has been considered a simple inverse correlation was observed between the coordinating power of the anion and the catalytic performance [88].…”
Section: Effect Of the Counteranionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cationic gold complexes with weakly coordinating counterions (which are often considered to be solvent-separated ions) [1][2][3], render powerful catalysts for the transformation of organic substrates [4][5][6], specifically the reactions of alkynes with a variety of heteroatom nucleophiles (Scheme 1) [7] such as water or alcohol [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], primary or secondary amines [23][24][25][26][27][28], or hydrazine [29][30][31]. These reactions are synthetically useful since gold catalysis is characterized by a good functional group tolerance for oxygen and nitrogen-containing molecules, which tend to be more difficult for catalytic transformations utilizing other transition metals [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%